Entangled Legalities Beyond the State - Krisch, Nico (Social Sciences, 2021)
This volume - featuring eminent contributors from law, political science, sociology, anthropology, history and political theory - shows that law is often better understood as an entangled web than a coherent system, analysing the ways in which different legalities in domestic, transnational and international law are connected.